Pedagogical interaction as a process and as a functional system - Kots, Myhailo Onysymovych (Аріельський університет (Аріель, Ізраїль), 2016)
Abstract. Kots M. O. Pedagogical interaction as a process and as a functional system. This article is a theoretical analysis of the phenomenon of pedagogical interaction as a process and as a functional system. It is proved that the necessary conditions of pedagogical interaction are: creation of the education developing space in school; availability of personal readiness of all educational activities for the implementation of educational impact and its realization in educational practice. It was proved that pedagogical interaction is a necessary functional system of educational process that occurs in the form of subject-subject interaction in which information is exchanged, also mental images of each other and form of interference, including the right balance of pedagogical impact, and its active perception.
Keywords: pedagogical interaction; padagogical communication; education; upbringing